UK surrogates' characteristics, experiences, and views on surrogacy law reform. (16th December 2022) - Horsey, Kirsty; Arian-Schad, Mimi; Macklon, Nicholas; Ahuja, Kamal
Abstract: What are surrogates' views on their experience with surrogacy, their understanding of the law, and views on legal reform? We conducted an online retrospective survey of women who underwent treatment as gestational surrogates in two UK-regulated IVF centres between March 2014 and October 2021. Forty-seven surrogates responded outlining their experiences with surrogacy in the England/Wales legal context, their understandings of the law, and thoughts on potential law reform. The surrogates ranged in age, occupation, and household income. Most surrogates were white, British women. While almost half were family members or friends of the intended parents, the largest category met the intended parents through a non-profit surrogacy organization. Two-thirds of the respondents had given birth to a baby as a surrogate. Surrogates generally do not view themselves as the mother of the child that they carry and support proposals for reforms that would recognize the intended parents as legal parents from birth. More ambivalence is apparent in relation to expenses and payments, though advertising is generally supported. Draft new legislation is expected to be introduced in the UK in 2023, and the results of this study could inform public and parliamentary debates to come in the UK and elsewhere. Moreover, the results from this survey can assist the development of good practice models for care on the surrogate pathway.